Brief geriatric assessments for older adults in the community in Singapore: a policy brief - Tan, Woan Shin; Gao, Jonathan; Ho, Ezra; Lau, Lay Khoon; Lun, Penny; Ding, Yew Yoong (Frontiers in Public Health, 2025)
Early detection and assessment of geriatric syndromes and social issues is important to help older adults maintain health and functional ability. While comprehensive geriatric assessment (CGA) is considered the gold standard, it is resource intensive to implement. Shorter forms such as a brief geriatric assessment (BGA) could be an alternative. We adopted a multi-method, three-phase study to understand how BGAs could be implemented in the community. Findings suggest that BGAs can help to identify older adults with unmet needs or geriatric syndromes for further appropriate assessments. A BGA should include an assessment of physical health, psychological health, functional ability, mobility, and social needs. Stakeholder dialogues emphasised that BGAs should align with the existing system of screening and assessments spearheaded by other governmental agencies.